THE REASONS FOR VACCINE HESITANCY TO THE MEASLES VACCINE: A QUICK REVIEW - Peres, Andréia Mura; Schwantes , Camila Ribeiro Martins; Candeia , Alinny Leite; Pamplona, Ysabely De Aguiar Pontes (Seven Editora, 2025)
Objective: To synthesize the evidence available in the scientific literature on the factors associated with measles vaccine hesitancy in children under two years of age, with a focus on the applicability of the findings to public health actions.Methods: A rapid review was carried out, using previously defined methodological shortcuts. The PubMed database was searched, with a 5-year time frame (2017-2022), restrictions on the languages Portuguese, English and Spanish, and only studies with free full text. Studies addressing vaccine hesitancy in children under two years of age were included.Results: The search resulted in 21 articles, of which 14 met the eligibility criteria. The main factors related to vaccine hesitancy were fear of adverse events, low confidence in the vaccine, misinformation, the influence of the internet and social networks, negative experiences with health services and social inequalities.Conclusion: Vaccine hesitancy must be tackled with strategies that involve clear, empathetic and evidence-based communication. It is essential to strengthen the bond with health services and educational actions to increase confidence in vaccines.DOI: https://doi.org/10.56238/sevened2025.021-033